Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
[tex]\displaystyle x=-\frac{2}{3}[/tex]
Step-by-step explanation:
We want to solve the equation:
[tex]\displaystyle \sqrt{x^2-4x+8}+x=2-x[/tex]
We can isolate the square root. Subtract x from both sides:
[tex]\sqrt{x^2-4x+8}=2-2x[/tex]
And square both sides:
[tex](\sqrt{x^2-4x+8})^2=(2-2x)^2[/tex]
Expand:
[tex]x^2-4x+8=4-8x+4x^2[/tex]
Isolate the equation:
[tex]3x^2-4x-4=0[/tex]
Factor:
[tex]\displaystyle (3x+2)(x-2)=0[/tex]
Zero Product Property:
[tex]3x+2=0\text{ or } x-2=0[/tex]
Solve for each case. Hence:
[tex]\displaystyle x=-\frac{2}{3}\text{ or } x=2[/tex]
Now, we need to check for extraneous solutions. To do so, we can substitute each value back into the original equation and check whether or not the resulting statement is true.
Testing x = -2/3:
[tex]\displaystyle \begin{aligned} \sqrt{\left(-\frac{2}{3}\right)^2-4\left(-\frac{2}{3}\right)+8}+\left(-\frac{2}{3}\right)&\stackrel{?}{=}2-\left(-\frac{2}{3}\right)\\ \\ \sqrt{\frac{4}{9}+\frac{8}{3}+8}-\frac{2}{3}&\stackrel{?}{=}2+\frac{2}{3} \\ \\ \sqrt{\frac{100}{9}}-\frac{2}{3}& \stackrel{?}{=} \frac{8}{3}\\ \\ \frac{10}{3}-\frac{2}{3} =\frac{8}{3}& \stackrel{\checkmark}{=}\frac{8}{3}\end{aligned}[/tex]
Since the resulting statement is true, x = -2/3 is indeed a solution.
Testing x = 2:
[tex]\displaystyle \begin{aligned}\sqrt{(2)^2-4(2)+8}+(2) &\stackrel{?}{=}2-(2) \\ \\ \sqrt{4-8+8}+2&\stackrel{?}{=}0 \\ \\ \sqrt{4}+2&\stackrel{?}{=}0 \\ \\ 2+2=4&\neq 0\end{aligned}[/tex]
Since the resulting statement is not true, x = 2 is not a solution.
Therefore, our only solution to the equation is x = -2/3.
Step-by-step explanation:
Hey there!
Given;
[tex] \sqrt{ {x}^{2} - 4x + 8} + x = 2 - x[/tex]
Take "X" in right side.
[tex] \sqrt{ {x - 4 + 8}^{2} } = 2 - 2x[/tex]
Squaring on both sides;
[tex] {( \sqrt{ {x}^{2} - 4x + 8 } )}^{2} = {(2 - 2x)}^{2} [/tex]
Simplify;
[tex] {x}^{2} - 4x + 8 = {(2)}^{2} - 2.2.2x + {(2x)}^{2} [/tex]
[tex] {x }^{2} - 4x + 8 = 4 - 8x + 4 {x}^{2} [/tex]
[tex]3 {x}^{2} - 4x - 4 = 0[/tex]
[tex]3 {x}^{2} - (6 - 2)x - 4 = 0[/tex]
[tex] 3 {x}^{2} - 6x + 2x - 4 = 0[/tex]
[tex]3x(x - 2) + 2(x - 2) = 0[/tex]
[tex](3x + 2)(x - 2) = 0[/tex]
Either;
3x+2 = 0
x= -2/3
Or;
x-2 = 0
x= 2
Check:
Keeping X= -2/3,
√(x²-4x+8 ) +X = 2-x
√{(-2/3)²-4*-2/3+8}+(-2/3) = 2+2/3
8/3 = 8/3 (True)
Now; Keeping X= 2
√{(2)²-4*2+8}+2 = 2-2
8 ≠0 (False)
Therefore, the value of X is -2/3.
Hope it helps!
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.